Sustainable Digital Marketing Strategies For MSMEs - Dessy Marhandrie (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to explore sustainable digital marketing strategies suitable for Micro, Small, and Medium Enterprises (MSMEs). The study employs a descriptive research model, utilizing purposive sampling to select participants with extensive experience in digital marketing within MSMEs. Data collection techniques include semi-structured interviews and content analysis of relevant literature. Thematic analysis will be employed to analyze the data, identifying patterns and themes related to effective sustainable digital marketing practices for MSMEs. The study anticipates uncovering insights into innovative and environmentally conscious digital marketing approaches that can be adopted by MSMEs to enhance their competitiveness while minimizing environmental impact.